Christian Muslim relations. a bibliographical history - Thomas, David 1948-; Chesworth, John (The History of Christian-Muslim Relations, 2017)
Christian-Muslim Relations, a Bibliographical History, Volume 11 (CMR 11) covering South and East Asia, Africa and the Americas in the period 1600-1700, is a continuing volume in a history of relations between the two faiths from the 7th to the early 20th century as this is reflected in written works. It comprises introductory essays and the main body of entries which treat all the works, surviving or lost, that are recorded. These entries provide biographical details of the authors, descriptions and assessments of their works, and complete accounts of publications and studies. The result of collaboration between numerous leading scholars, CMR 11 , along with the other volumes in this series, is intended as a basic tool for research in Christian-Muslim relations. Section Editors: Clinton Bennett, Luis F. Bernabe Pons, Jaco Beyers, Lejla Demiri, Martha Frederiks, David D. Grafton, Stanisław Grodź, Alan Guenther, Emma Gaze Loghin, Gordon Nickel, Claire Norton, Reza Pourjavady, Douglas Pratt, Radu Păun, Peter Riddell, Umar Ryad, Mehdi Sajid, Cornelia Soldat, Karel Steenbrink, Davide Tacchini, Ann Thomson, Serge Traore, Carsten Walbiner